Blood lipid levels, lipid-lowering medications, and the incidence of atrial fibrillation: The atherosclerosis risk in communities study - Lopez, F.; Agarwal, S.; MacLehose, R.; Soliman, E.; Sharrett, A.; Huxley, Rachel; Konety, S.; Ballantyne, C.; Alonso, A. (2012)
Background-Several cardiovascular risk factors have been associated with the risk of atrial fibrillation (AF). Limited and inconsistent evidence exists on the association of blood lipid levels and lipid-lowering medication use with AF risk. Methods and Results-We analyzed 13 969 participants (25% African American, 45% men) free of AF at baseline from the Atherosclerosis Risk in Communities study. Fasting high-density lipoprotein cholesterol (HDLc), low-density lipoprotein cholesterol (LDLc), triglycerides, and total cholesterol were measured at baseline (1987-1989) and each of 3 follow-up visits. The incidence of AF was ascertained through 2007. The association of the use of statins and other lipid-lowering medications with AF was estimated in 13 044 Atherosclerosis Risk in Communities participants attending visit 2 (1990 -1992), adjusting for covariates from the previous visit. During a median follow-up of 18.7 years, there were 1433 incident AF cases. Multivariable hazard ratios (HRs) and 95% CIs of AF associated with a 1-SD increase in lipid levels were as follows: HDLc, 0.97 (0.91-1.04); LDLc, 0.90 (0.85- 0.96); total cholesterol, 0.89 (0.84-0.95); and triglycerides, 1.00 (0.96 -1.04). Participants taking lipid-lowering medications had an adjusted HR (95% CI) of AF of 0.96 (0.82-1.13) compared with those not taking medications, whereas those taking statins had an adjusted HR of 0.91 (0.66 -1.25) compared with those taking other lipid-lowering medications. Conclusions-Higher levels of LDLc and total cholesterol were associated with a lower incidence of AF. However, HDLc and triglycerides were not independently associated with AF incidence. No association was found between the use of lipid-lowering medications and incident AF. © 2012 American Heart Association, Inc.